Crystal structure of K[PtCl3(caffeine)] and its interactions with important nitrogen-donor ligands. Issue 5 (3rd March 2016) - Jovanović, Snežana; Puchta, Ralph; Klisurić, Olivera; Bugarčić, Živadin D.
Abstract: The crystal structure of K[PtCl3 (caffeine)] was determined. The coordination geometry around platinum is square-planar formed by N9 of the caffeine ligand and three Cl − ions. The bond lengths and angles of K[PtCl3 (caffeine)] were compared with those reported for [PtCl3 (caffeine)] − and K[PtCl3 (theobromine)]. At the level of the statistical significance of the data we have compared, no differences in the bond distances and angles for any of these compounds were noticed. Weak interactions between K + and Cl − are responsible for the formation of 1-D polymeric chains in the crystal structure of the complex. The interactions of K[PtCl3 (caffeine)] with inosine (Ino) and guanosine-5′-monophosphate (5′-GMP) were studied by 1 H NMR spectroscopy at 295 K in D2 O in a molar ratio of 1 : 1. The results indicate formation of the reaction product [PtCl3 (Nu)] (Nu=Ino or 5′-GMP) with the release of caffeine from the coordination sphere of the starting complex. The higher stability of the bond between the Pt(II) ion and Ino or 5′-GMP compared to the stability of the platinum–caffeine bond is confirmed by density functional theory calculations (B3LYP/LANL2DZp) using as models 9-methylhypoxanthine and 9-methylguanine. Abstract :